2008
DOI: 10.1038/ni.1662
|View full text |Cite
|
Sign up to set email alerts
|

The actin regulator coronin 1A is mutant in a thymic egress–deficient mouse strain and in a patient with severe combined immunodeficiency

Abstract: Mice carrying the recessive peripheral T cell deficiency (Ptcd) locus have a block in thymic egress but the mechanism responsible is undefined. Here we found that Ptcd T cells have an intrinsic migration defect, impaired lymphoid tissue trafficking and irregularly shaped protrusions. Characterization of the Ptcd locus revealed an E26K point mutation within the actin regulator coronin-1A (Coro1a) that enhanced its inhibition of the actin regulator Arp2/3 and resulted in its mislocalization from the leading edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
261
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(271 citation statements)
references
References 39 publications
6
261
3
1
Order By: Relevance
“…We demonstrate that increased polymerized actin is associated with a unique dysfunction of lymphocytes, including decreased cell spreading and increased apoptosis. Two recent papers show that deficiency in coronin1A, a negative regulator of actin dynamics, leads to increased polymerized actin in thymocytes and T cells associated with increased apoptosis (Föger et al, 2006;Shiow et al, 2008). Although coronin1A-deficient thymocytes and T cells have a decreased capacity to migrate to chemokines in vitro and fail to egress normally from the thymus (Föger et al, 2006;Shiow et al, 2008), our results show that WASP-I296T B and T cells migrate normally to chemokines.…”
Section: Wasp-i296t and Wasp-l272p Are Expressed In B And T Cells Andmentioning
confidence: 45%
See 1 more Smart Citation
“…We demonstrate that increased polymerized actin is associated with a unique dysfunction of lymphocytes, including decreased cell spreading and increased apoptosis. Two recent papers show that deficiency in coronin1A, a negative regulator of actin dynamics, leads to increased polymerized actin in thymocytes and T cells associated with increased apoptosis (Föger et al, 2006;Shiow et al, 2008). Although coronin1A-deficient thymocytes and T cells have a decreased capacity to migrate to chemokines in vitro and fail to egress normally from the thymus (Föger et al, 2006;Shiow et al, 2008), our results show that WASP-I296T B and T cells migrate normally to chemokines.…”
Section: Wasp-i296t and Wasp-l272p Are Expressed In B And T Cells Andmentioning
confidence: 45%
“…Two recent papers show that deficiency in coronin1A, a negative regulator of actin dynamics, leads to increased polymerized actin in thymocytes and T cells associated with increased apoptosis (Föger et al, 2006;Shiow et al, 2008). Although coronin1A-deficient thymocytes and T cells have a decreased capacity to migrate to chemokines in vitro and fail to egress normally from the thymus (Föger et al, 2006;Shiow et al, 2008), our results show that WASP-I296T B and T cells migrate normally to chemokines. This indicates that in addition to increased polymerized actin in WASP-I296T B and T cells (which is also appreciated in cononin1A-deficient cells), constitutive activation of WASP WASP-deficient cells (Fig.…”
Section: Wasp-i296t and Wasp-l272p Are Expressed In B And T Cells Andmentioning
confidence: 45%
“…In the absence of NPFs, Arp2/3 complex has weak or no nucleation activity. However, inhibitors of Arp2/3 complex play important roles in controlling the activity of the complex in vivo (7)(8)(9)(10)(11), suggesting that multiple layers of regulation of Arp2/3 complex are required for controlling the assembly of cellular actin networks.…”
mentioning
confidence: 99%
“…Recent studies have also demonstrated that p57/coronin-1 was enriched in immunological synapses and involved in various immune regulatory functions such as signal transduction via T cell receptors (16 -18), survival of T cells (19,20), and intracellular Ca 2ϩ mobilization in T and B cells (19,21). More recently, it was reported that the p57/coronin-1 gene was responsible for human and mouse severe combined immunodeficiency (22,23). In mice deficient in the p57/coronin-1 gene, differentiation and chemokine-mediated trafficking of T cells were severely impaired (22,24,25).…”
mentioning
confidence: 99%
“…More recently, it was reported that the p57/coronin-1 gene was responsible for human and mouse severe combined immunodeficiency (22,23). In mice deficient in the p57/coronin-1 gene, differentiation and chemokine-mediated trafficking of T cells were severely impaired (22,24,25). It was further demonstrated that the developments of experimental autoimmune encephalomyelitis (26,27) and lupus-like autoimmune disease (28) were suppressed in mice with genetic defects of p57/coronin-1.…”
mentioning
confidence: 99%